2000
DOI: 10.1097/00006254-200010000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of 72 Pregnancies in 55 Women With Cystic Fibrosis in the United Kingdom 1977???1996

Abstract: Objective To identify pregnancies in women with cystic fibrosis and describe obstetric, infant and maternal medical outcomes in relation to the severity of maternal disease. Design Retrospective study, based on casenotes. Setting Eleven cystic fibrosis centres in the United Kingdom. Population Pregnant women with cystic fibrosis. Methods Single observer medical and obstetric casenote review categorising maternal cystic fibrosis (e.g. genotype, pancreatic, hepatic and diabetic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
8
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(96 citation statements)
references
References 0 publications
3
74
8
11
Order By: Relevance
“…13 Studies have reported a direct relationship between maternal FEV1 during pregnancy and infant birthweight, 14,15 and an inverse relationship with intrauterine growth retardation, 14 gestational hypertension, and preterm birth in asthmatic women. 15 In pregnant women with cystic fibrosis, low FEV1 is associated with preterm delivery, [16][17][18] and with a greater loss of lung function during pregnancy. 17,18 As a consequence, pregnant women with pulmonary disease need regular monitoring of symptoms and measures of lung function by spirometry in order to optimise their lung function throughout pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…13 Studies have reported a direct relationship between maternal FEV1 during pregnancy and infant birthweight, 14,15 and an inverse relationship with intrauterine growth retardation, 14 gestational hypertension, and preterm birth in asthmatic women. 15 In pregnant women with cystic fibrosis, low FEV1 is associated with preterm delivery, [16][17][18] and with a greater loss of lung function during pregnancy. 17,18 As a consequence, pregnant women with pulmonary disease need regular monitoring of symptoms and measures of lung function by spirometry in order to optimise their lung function throughout pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…The respiratory parameter most frequently described as being predictive of outcome is the forced expiratory volume in 1 s (FEV 1 ). Thresholds vary -different studies have linked poorer outcome with figures of less than 50% [4], 60% [5] or 70% [6] of predicted. Gilljam et al [4] also noted that infection with Burkholderia cepacia was associated with a poorer outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Gilljam et al [4] also noted that infection with Burkholderia cepacia was associated with a poorer outcome. Others have advised against pregnancy in a context of pulmonary hypertension or cor pulmonale [6].…”
Section: Discussionmentioning
confidence: 99%
“…23 In a study of 26 term and 22 preterm live deliveries in women with CF the mean maternal weight gain of those pregnancies reaching term was 8.9 kg and only 2.6 kg in those delivering prematurely. 24 Careful consideration should be given to appropriate vitamin supplementation. Folic acid should ideally be used for 3 months preconceptually and for the first trimester of pregnancy to reduce the risk of fetal neural tube defects.…”
Section: Physiology Of Pregnancymentioning
confidence: 99%
“…24 Fourteen (20%) pregnancies were terminated. The data showed that the prepregnancy %FEV 1 and %FVC predicted were significantly associated with gestational age, maternal weight gain and infant birthweight.…”
Section: Pregnancy and Cystic Fibrosismentioning
confidence: 99%